If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = b + s Solving 23 = b + s Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 23 + -1b = b + -1b + s Combine like terms: b + -1b = 0 23 + -1b = 0 + s 23 + -1b = s Add '-23' to each side of the equation. 23 + -23 + -1b = -23 + s Combine like terms: 23 + -23 = 0 0 + -1b = -23 + s -1b = -23 + s Divide each side by '-1'. b = 23 + -1s Simplifying b = 23 + -1s
| 5x(10)=81 | | N(10)+N(5)+N(0)+N(23)+N(10)= | | 15=51c-13 | | 35=-6t-7 | | -4x+5=5+7x | | (4n+13)8=6n | | 3a+3=5a-9 | | R+14=3 | | 12v+10v+14=18 | | 3x=0.008 | | c+21-10c=5-14c+16 | | 42=7z-21 | | 3x+8-9x=-20 | | n-12=5n | | 2x-7y=y | | 3m+8+m=6m | | 25.24=5y+3.87 | | -3y-7(-8y+1)=-6-8(7-y) | | Sin(2x+20)=cos(3x-30) | | 8(x+8)+2=-7(x-5)-3 | | 8=x^2-6x | | 7-6x=-8 | | -5(x+8)-3x= | | 7(1-2)-3=4-2 | | 7.68*7.68= | | 9(x-2)-2(x-2)=28 | | (3069+x)1/3=1500 | | 9(x-2)-2(x+2)=28 | | -12+6x=6+5(x-5)+8 | | 4s-10=38 | | 13x-(5x-11)=53 | | 180-x=2(180-(90-x)) |